Asháninca narratives and their processes on the border between Brazil and Peru - Mesquita, Érika (2017)
This article discusses the narratives and representations the some experiences that the tribe Asháninca that live in Brazil. The myths are complex and also the processes that the Asháninca are developing for the understanding of the phenomena in their daily life. We focus our attention on the context of some of his knowledge, particularly those referring to his cosmology, which integrates viewpoints of many worlds, mixing fantastic figures and supernatural appearances with the presentation of some representation of the narrated versions of Its history and the knowledge acquired also through the master plants in their habitat: the border region of the forest between Brazil and Peru.